Analisis Kesulitan Siswa Dalam Belajar Matematika Menggunakan Kurikulum 2013 di SMPN 1 Kota Bengkulu - Effendi, Herlina; Maryani, Maryani; Henky Sabantro (Yayasan Darussalam Bengkulu, 2020)
This study aims to determine the difficulties of students in working on questions on triangle material in class VII. As for the factors that cause difficulties in solving problems for students and internal factors or factors from within themselves and external factors, namely factors that arise from outside the student. This type of research is qualitative research that produces descriptive data. The subjects of this study were students of SMP 1 Bengkulu City, which consisted of 7 students in class VII.4 for the 2020 school year. Data collection techniques used are tests, observation, interviews and documentation. The data analysis technique used is qualitative including: data reduction, data presentation (data display) and conclusion drawing. After being analyzed and seen from the explanation of the table above, it is evident that the most types of errors are types of conceptual errors. This error occurs because of an error using the triangle formula in mathematics lessons. The factors of the difficulties experienced by students are not being careful, rushing in working on the questions, forgetting, not having enough time to do the questions, giving up quickly, being fooled, and anxious.